Current practice patterns, challenges, and educational needs of asthma care providers in the United States. (3rd August 2021) - Singh, Siddhartha; Surani, Salim; McGuinness, Sue; Eudicone, James; Gilbert, Ileen; Subramanian, Shyam
Abstract: Objective: For severe, uncontrolled asthma (SUA), a gap exists between recent scientific advances and their incorporation into clinical practice. Using a Knowledge-to-Action Framework, new knowledge can be translated into evidence-based interventions to improve outcomes. The AstraZeneca U.S. PRECISION initiative aims to apply this Framework to improve recognition and management of SUA. The study objective was to identify factors contributing to gaps in care for patients with SUA. Results from a needs assessment survey of U.S. pulmonologists and allergists/immunologists were assessed within the Knowledge-to-Action Framework to advance bench-to-bedside care. Methods: Pulmonologists and allergists/immunologists from across the United States were invited to complete a customized, quantitative severe asthma survey in person at the 2017 American Thoracic Society annual meeting or via the Internet. Responses were summarized descriptively, and chi-squared tests evaluated associations between variables of interest. Results: Overall, 140 U.S. providers responded, most of whom were pulmonologists (84%). Most (60%) practiced in a community-based setting; 40% practiced at an academic medical center. Key challenges to providing care for patients with severe asthma included insurance company requirements and identification of the pathophysiology of an individual patient's severe asthma. Traditional measures of asthma-related morbidity were ranked as highly important by significantly more respondents compared with assessment of biomarkers ( p  < 0.0001). Respondents generally valued online virtual self-education. Conclusions: Survey results identified unmet needs for the identification and management of patients with SUA and opportunities to improve patient outcomes through evidence-based management of SUA, including testing for biologic eligibility and subsequent use of biologic therapies.